Efficacy of phosphatidic acid ingestion on lean body mass, muscle thickness and strength gains in resistance-trained men - Hoffman Jay R; Stout Jeffrey R; Williams David R; Wells Adam J; Fragala Maren S; Mangine Gerald T; Gonzalez Adam M; Emerson Nadia S; McCormack William P; Scanlon Tyler C; Purpura Martin; Jäger Ralf (Taylor & Francis Group, 2012)
Abstract Background Phosphatidic acid (PA) has been reported to activate the mammalian target of rapamycin (mTOR) signaling pathway and is thought to enhance the anabolic effects of resistance training. The purpose of this pilot study was to examine if oral phosphatidic acid administration can enhance strength, muscle thickness and lean tissue accruement during an 8-week resistance training program. Methods Sixteen resistance-trained men were randomly assigned to a group that either consumed 750 mg of PA (n = 7, 23.1 ± 4.4 y; 176.7 ± 6.7 cm; 86.5 ± 21.2 kg) or a placebo (PL, n = 9, 22.5 ± 2.0 y; 179.8 ± 5.4 cm; 89.4 ± 13.6 kg) group. During each testing session subjects were assessed for strength (one repetition maximum [1-RM] bench press and squat) and body composition. Muscle thickness and pennation angle were also measured in the vastus lateralis of the subject's dominant leg. Results Subjects ingesting PA demonstrated a 12.7% increase in squat strength and a 2.6% increase in LBM, while subjects consuming PL showed a 9.3% improvement in squat strength and a 0.1% change in LBM. Although parametric analysis was unable to demonstrate significant differences, magnitude based inferences indicated that the Δ change in 1-RM squat showed a likely benefit from PA on increasing lower body strength and a very likely benefit for increasing lean body mass (LBM). Conclusions Results of this study suggest that a combination of a daily 750 mg PA ingestion, combined with a 4-day per week resistance training program for 8-weeks appears to have a likely benefit on strength improvement, and a very likely benefit on lean tissue accruement in young, resistance trained individuals.